„Jest ja, ale mnie nie ma” – granica poetyckiego szaleństwa Rafała Wojaczka - Pertek, Grzegorz (Wydawnictwo Naukowe UAM w Poznaniu, 2011)
In this article the author made an attempt at demarcating the limits of the poetic language of Rafał Wojaczek, the crossing of which – as the author of this study thinks – opens before the poet a possibility of achieving the perfectness of the subject of his poems, portending the specter of madness. This project is combined with the problems of the crisis of identity being both the reason and the consequence of the many renewed attempts at its realisation. The author claims that from this point of view, it was in the Dziennik [Diary] (the first of the analysed texts) Wojaczek as an author his desire of perfection and discovers that it is unattainable beyond madness. Dziennik is also a place of the first experience of the crisis in view of which the debut Sezon [Season], and in particular the poem which opens that book, and which has the same title as the whole (another text submitted to interpretaion), is only its poetic rewriting. Such a view allows the author to reveal the intertextual opening. In the course of analysis of the poem, difficulties connected with the realisation of the project, i.e. obtaining oneself as authentic in the language, just defining of identity, the source of which is Arthur Rimbaud’s philosophy, is exposed. Nevertheless Wojaczek’s subject is neither a repetition of the model of Rimbaud nor its denial, but a transfer of elusiveness of the changeable “I”, expressed by means of the formula “I is someone else”, into the area of absence. The considerations are capped with the interpretation of the work Piszę wiersz [I am writing a poem], which is a poetic verification of diagnoses made by Wojaczek in Sezon.
“There is I, but me is not” – the limits of poetic madness of Rafał Wojaczek